2016
DOI: 10.1007/s12539-016-0149-8
|View full text |Cite
|
Sign up to set email alerts
|

Herbal Lead as Ideal Bioactive Compounds Against Probable Drug Targets of Ebola Virus in Comparison with Known Chemical Analogue: A Computational Drug Discovery Perspective

Abstract: Ebola is a deadly virus that has recently emerged as an enormous public health concern which causes dangerous illness with high fatality rates of 90 %. The virus is not receptive to known antivirals, and hence, there is a promising need to identify novel inhibitors to combat the disease. The present study deals with identification of potential herbal leads that probably subdue the activity of four major drug targets of Ebola virus such as VP24, VP30, VP35 and VP40 by computer-aided virtual screening. The selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 57 publications
1
29
0
Order By: Relevance
“…Consequently, such compounds should be removed to prevent possible toxicity during early stages of drug development [61]. Limonin [62] and Neoglucobrassicin [63] were predicted as anti-Ebola compounds but showed high-risk structural alerts, including (a) high-risk epoxides that form protein adducts, thus potentially disturbing signal transduction cascades [64] and (b) high-risk quinones that lead to the formation of reactive oxygen species (ROS) and cause severe oxidative stress [65]. Furthermore, quinone-like compounds comprise structures that are widely reported to yield false positives or are inactive [60].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, such compounds should be removed to prevent possible toxicity during early stages of drug development [61]. Limonin [62] and Neoglucobrassicin [63] were predicted as anti-Ebola compounds but showed high-risk structural alerts, including (a) high-risk epoxides that form protein adducts, thus potentially disturbing signal transduction cascades [64] and (b) high-risk quinones that lead to the formation of reactive oxygen species (ROS) and cause severe oxidative stress [65]. Furthermore, quinone-like compounds comprise structures that are widely reported to yield false positives or are inactive [60].…”
Section: Discussionmentioning
confidence: 99%
“…Another docking study performed by Setlur et al suggested that herbal leads limonin ( Figure 5) and gummosin reported high predicted binding energy of -9.7 kcal/mol and -9.1 kcal/mol, respectively, for both VP35 (PDB ID: 4IJE) and VP24 (PDB ID: 4M0Q) [124]. In addition, samarcandin were reported to have high docked energy (-9.4 kcal/mol) in complex with VP24, while polyanthin (-9.0 kcal/mol) with VP35 (Setlur, Naik, and Skariyachan 2016).…”
Section: Plant Extracts and Natural Compoundsmentioning
confidence: 98%
“…However, the refinement of the model often does not meet the desired level of accuracy . A number of potential in silico studies have been documented over last few years which include homology modeling of unresolved EBOV polymerase and docking‐based virtual screening of compounds that have potential to bind with important residues lining the binding pocket of EBOV VP40, VP24, VP30, and VP35 …”
Section: Introductionmentioning
confidence: 99%